Transfer of technology to developing countries : unilateral and multilateral policy options - Hoekman, Bernard M. (2005)
analyzes national and international policyoptions to encourage the international transfer of technology, distinguishing between foru major channels of such transfer: trade in products; trade in knowledge and technology; foreign direct investment; and, intranational and international movement of people.